THE INFLUENCE OF EARNINGS MANAGEMENT AND AUDIT QUALITY ON FERC WITH FINANCIAL PERFORMANCE AS MODERATION - sofie, Sofie; Murwaningsari, Etty (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The aim of this research is to examine the influence of earnings management, auditor quality on the Future Earning Response Coefficient, moderated by Financial Performance and Size and CAR as control variables . This research uses secondary data in the form of banking sector financial reports listed on the IDX in 2017-2022. The number of samples used in the research was 41 companies, so the total observations were 205 financial reports. Panel data analysis method using Eviews. The results of this research prove that 1) Earning Management has supported to have a positive and significant effect on FERC; 2) Audit quality is supported to have a positive effect on FER; 3) ROE is not proven to be a moderating variable in the FERC function so that the influence of EM and KA which are moderated by ROE on FERC is not supported.